Conservation status of freshwater mussels in Europe: state of the art and future challenges - Lima, Manuel Lopes (2017)
Freshwater mussels of the Order Unionida provide important ecosystem functions and services, yet many of their populations are in decline. We comprehensively review the status of the 16 currently recognized species in Europe, collating for the first time their life-history traits, distribution, conservation status, habitat preferences, and main threats in order to suggest future management actions. In northern, central, and eastern Europe, a relatively homogeneous species composition is found in most basins. In southern Europe, despite the lower species richness, spatially restricted species make these basins a high conservation priority. Information on freshwater mussels in Europe is unevenly distributed with considerable differences in data quality and quantity among countries and species. To make conservation more effective in the future, we suggest greater international cooperation using standardized protocols and methods to monitor and manage European freshwater mussel diversity. Such an approach will not only help conserve this vulnerable group but also, through the protection of these important organisms, will offer wider benefits to freshwater ecosystems.